Enhancing Students' Speaking Ability Using Story Telling Technique: An Action Research - Azkiyyah, Salsabilla Dziky; Sutiyono, Akhmad; Subari, Imam (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2019)
This research aimed to improve the students' speaking skills through Story Telling. This research aimed to identify whether implementing Story Telling can improve students' speaking skills and learning activities focused on descriptive text. The researchers used classroom action research. The research implementation was in 2 cycles in one class with 20 students. For the data collecting technique, the researchers used observation and tests. In analyzing the data, the researchers used descriptive analysis. The findings of this research showed that after teaching reading through Story Telling. The researchers found that Story Telling successfully improves students' speaking skills and learning activities. It can be seen from the average score of students' speaking skills. It was increased from cycle I to cycle II. The researchers found that the average score of students who passed the Minimum Mastery Criteria in cycle I was 45%, while in cycle II obtained 85%. The mean score of cycle I was 55.8, and cycle II was 71.3. The students' learning activity was also increased from the first cycle, 6.17, categorized as less active, while in the second cycle, 7.92, classified as active. Therefore, it can be concluded that the implementation of Story Telling can improve the student's speaking skills and the student learning activity in the tenth grade of SMP Negeri 14 Bandar Lampung in the academic year of 2018/2019.